2022
DOI: 10.3390/ma15051807
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Reactive Powder Concrete with Coal Gangue as Sand Replacement

Abstract: Coal gangue (CG) represents a huge amount of industrial solid waste in China, and usually is used as a coarse aggregate to produce low-strength coal-gangue-based concrete. In this paper, in order to prove the possibility to obtain a higher-strength concrete with a higher CG utilization rate, reactive powder concrete (RPC) with coal gangue as a sand replacement at different replacement ratios was studied. RPC samples were prepared by replacing natural river sand (RS) with CG sand at different CG/RS weight ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, the eco-friendly utilization of coal gangue becomes an urgent issue. Extensive research has demonstrated that coal gangue can be effectively used as a substitute for partial cementitious powder, fine or coarse aggregate in concrete, which not only alleviates the problem of deposited coal gangue but also reduces the exploitation of river sand and natural gravel [ 4 ]. Yu, et al [ 5 ] used coal gangue to entirely replace fine and coarse aggregate, preparing coal gangue concrete (CGC) of C30–C50 grade.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the eco-friendly utilization of coal gangue becomes an urgent issue. Extensive research has demonstrated that coal gangue can be effectively used as a substitute for partial cementitious powder, fine or coarse aggregate in concrete, which not only alleviates the problem of deposited coal gangue but also reduces the exploitation of river sand and natural gravel [ 4 ]. Yu, et al [ 5 ] used coal gangue to entirely replace fine and coarse aggregate, preparing coal gangue concrete (CGC) of C30–C50 grade.…”
Section: Introductionmentioning
confidence: 99%
“…It is more durable and also has better mechanical properties than regular concrete [2,3]. Wen L., et al [4] investigation focused on the mechanical and micro structural characteristics of RPC samples. In order to create RPC samples, coal gangue sand was substituted for natural river sand at various weight ratios ranging from 0 to 100% at intervals of 25%.…”
Section: Introductionmentioning
confidence: 99%
“…There is a sort of material that can be utilized not only as a substitute for cement clinker, but also as a substitute for natural raw materials for the production of building materials [6][7][8][9]. In conjunction with the rapid increase in concrete production, the demands for natural aggregates are also increasing.…”
Section: Introductionmentioning
confidence: 99%